A method for producing high performance aluminum alloys using recycled aluminum

CN117802339BActive Publication Date: 2026-10-13SHANDONG INNOVATION METAL TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311569700.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-23
Publication Date
2026-10-13
Estimated Expiration
2043-11-23

AI Technical Summary

Benefits of technology

1、本发明以网状增强颗粒为增强体,网状增强颗粒不仅具有很好的强度,并具有很好的韧性,网状结构能够在铝合金中分散更均匀,同时与再生铝合金的结合更佳,同时网状增强颗粒中的钛可以使再生铝的晶粒明显细化,由粗大的柱状晶变成等轴晶,提高力学性能。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application provides a method for producing high-performance aluminum alloy by using recycled aluminum. The method comprises the following steps: step 1: taking the nitrogen-atomized recycled aluminum alloy material, adding Fe elements and La elements, and performing planetary ball milling; step 2: drying the powder after ball milling in air, adding mesh reinforcement particles with a particle size of 0.1-1 mu m, and uniformly mixing; step 3: cold isostatic pressing under a pressure of 100 MPa; and step 4: sintering at 600-650 DEG C for 5 h in a nitrogen atmosphere, and hot extrusion molding at 450 DEG C. The mesh reinforcement particles are used as the reinforcing body, the mesh reinforcement particles have good strength and good toughness, the mesh structure can be more uniformly dispersed in the aluminum alloy, the combination with the recycled aluminum alloy is better, meanwhile, titanium in the mesh reinforcement particles can obviously refine the grains of the recycled aluminum, the coarse columnar crystals are changed into equiaxed crystals, and the mechanical properties are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aluminum alloy materials technology, and more specifically to a method for producing high-performance aluminum alloys using recycled aluminum. Background Technology

[0002] Aluminum is the most consumed non-ferrous metal and an important functional and structural material for national economic development. It is one of the most widely used and economical materials currently available. Recycled aluminum consumes only 5% of the energy of primary aluminum and emits only 5.8% of greenhouse gases. One ton of recycled aluminum can also save 1.9 tons of alumina, meaning that recycling waste aluminum can effectively reduce aluminum shortages. However, the initial properties of recycled aluminum are not good and it cannot be used directly. It must be processed and modified to improve its properties before it can be used. Therefore, producing a high-performance aluminum alloy from recycled aluminum is an urgent problem to be solved. Summary of the Invention

[0003] Technical problem to be solved: In view of the above-mentioned technical problems, the purpose of this invention is to provide a method for producing high-performance aluminum alloys using recycled aluminum, with mesh-reinforced particles as the reinforcement. The mesh-reinforced particles not only have good strength but also good toughness. The mesh structure can be more uniformly dispersed in the aluminum alloy and has better bonding with the recycled aluminum alloy. At the same time, the titanium in the mesh-reinforced particles can significantly refine the grains of the recycled aluminum, changing them from coarse columnar crystals to equiaxed crystals, thereby improving mechanical properties.

[0004] Technical solution: A method for producing high-performance aluminum alloys using recycled aluminum, characterized by comprising the following steps: Step 1: Take the recycled aluminum alloy material after nitrogen atomization, add Fe and La elements, and perform planetary ball milling; Step 2: After ball milling, the powder is dried in air, and then mesh reinforcing particles with a particle size of 0.1-1μm are added and mixed evenly. Step 3: Cold isostatic pressing at 100 MPa pressure; Step 4: Sinter at 600-650℃ for 5 h in a nitrogen atmosphere, and then hot extrude at 450℃.

[0005] Furthermore, the composition of the recycled aluminum alloy is as follows: Ti 0.20wt.% Mn 0.11wt.% Si 4.22wt.% Mg 0.78 wt.% Fe 0.02wt.% Cu 0.21 wt.% Al represents the remaining amount.

[0006] Furthermore, the Fe element has a particle size of <48μm, and the La element has a particle size of <30μm.

[0007] Furthermore, the Fe element content accounts for 3.2 wt.% of the recycled aluminum alloy material, and the La element content accounts for 1.0-1.5 wt.% of the recycled aluminum alloy material.

[0008] Furthermore, the ball milling time is 5 hours, the ball-to-material ratio is 10:1, the ball milling medium is acetone, and the rotation speed is 150 rpm.

[0009] Furthermore, the mass ratio of the recycled aluminum alloy to the mesh reinforcing particles is (4-7):100.

[0010] Furthermore, the preparation method of the mesh-reinforced particles is as follows: S1: Take carbon nanotubes, soak them in a mixed acid solution for acidification for 5-7 hours, wash and dry them to obtain acidified carbon nanotubes. S2: Prepare a titanium powder hydrochloric acid solution with a mass fraction of 3-10% and a carbon nanotube aqueous solution with a mass fraction of 3-7% and a pH value of 3-5. Add the acidified carbon nanotube aqueous solution to the titanium powder hydrochloric acid solution under stirring, and adjust its pH value to 3-5 with hydrochloric acid. S3: Transfer to a reaction vessel ventilated with oxygen, react at 40-60℃ for 20-30 hours, then filter and dry; S4: Place it in a tube furnace filled with hydrogen and react at 250-350℃ for 2-8 hours. After cooling, place it in a sintering furnace and hold it at 500-900℃ and 100-200MPa for 0.5-1 hours. After cooling and crushing, the mesh-reinforced particles are obtained.

[0011] Furthermore, the extrusion speed of the hot extrusion molding is 0.5 m / min.

[0012] Furthermore, the mixed acid solution is prepared by mixing concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:(2-4).

[0013] Furthermore, the mass ratio of the titanium powder to the acidified carbon nanotubes is 20:(0.5-3).

[0014] Beneficial effects: 1. This invention uses mesh-reinforced particles as reinforcement. The mesh-reinforced particles not only have good strength but also good toughness. The mesh structure can be more uniformly dispersed in aluminum alloys and has better bonding with recycled aluminum alloys. At the same time, the titanium in the mesh-reinforced particles can significantly refine the grains of recycled aluminum, changing them from coarse columnar crystals to equiaxed crystals, thereby improving mechanical properties.

[0015] 2. In this invention, Fe element is added (the Fe element content in recycled aluminum alloy is low, and the fine grain strengthening and precipitation strengthening of Fe element can make up for the deficiency), which can improve toughness. At the same time, the addition of La element can refine the grain and improve the mechanical properties of aluminum alloy materials.

[0016] 3. In this invention, carbon nanotubes are adsorbed onto the surface of titanium powder by electrostatic force, and in Cl... - Under the corrosive effect, titanium oxide particles are generated in situ on the surface of titanium powder. Titanium powder can form a tight nest with carbon nanotubes. Then, through hydrogen reduction and sintering, network-reinforced particles are obtained.

[0017] 4. This invention utilizes the strengthening effect of the "enriched region" of carbon nanotubes and the toughening effect of the "depleted region" of carbon nanotubes to enable the network-reinforced particles to maintain good plasticity while improving strength. Detailed Implementation

[0018] This invention proposes a method for producing high-performance aluminum alloys using recycled aluminum. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the following will provide a more detailed description of the invention in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.

[0019] Example 1 The preparation method of the network-reinforced particles is as follows: S1: Take carbon nanotubes, soak them in a mixed acid solution for acidification for 5 hours, wash and dry them to obtain acidified carbon nanotubes; wherein, the mixed acid solution is prepared by mixing concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:2; S2: Prepare a 3% (w / w) titanium powder hydrochloric acid solution with a pH of 3 and a 3% (w / w) acidified carbon nanotube aqueous solution. Add the acidified carbon nanotube aqueous solution to the titanium powder hydrochloric acid solution while stirring, and adjust the pH to 3 with hydrochloric acid. The mass ratio of titanium powder to acidified carbon nanotubes is 20:0.5. S3: Transfer to a reaction vessel ventilated with oxygen, react at 40°C for 20 hours, then filter and dry; S4: Placed in a tube furnace filled with hydrogen, reacted at 250℃ for 2 hours, cooled and then placed in a sintering furnace, held at 500℃ and 100MPa for 0.5 hours, cooled and crushed to obtain network-reinforced particles.

[0020] Example 2 The preparation method of the network-reinforced particles is as follows: S1: Take carbon nanotubes, soak them in a mixed acid solution for acidification for 5 hours, wash and dry them to obtain acidified carbon nanotubes; wherein, the mixed acid solution is prepared by mixing concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:2; S2: Prepare a 5% (w / w) titanium powder hydrochloric acid solution with a pH of 3 and a 4% (w / w) acidified carbon nanotube aqueous solution. Add the acidified carbon nanotube aqueous solution to the titanium powder hydrochloric acid solution with stirring, and adjust the pH to 3 with hydrochloric acid. The mass ratio of titanium powder to acidified carbon nanotubes is 20:1. S3: Transfer to a reaction vessel ventilated with oxygen, react at 40°C for 20 hours, then filter and dry; S4: Placed in a tube furnace filled with hydrogen, reacted at 250℃ for 4 hours, cooled and then placed in a sintering furnace, held at 600℃ and 100MPa for 0.5 hours, cooled and crushed to obtain network-reinforced particles.

[0021] Example 3 The preparation method of the network-reinforced particles is as follows: S1: Take carbon nanotubes, soak them in a mixed acid solution for acidification for 6 hours, wash and dry them to obtain acidified carbon nanotubes; wherein, the mixed acid solution is prepared by mixing concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:3; S2: Prepare a 6% (w / w) titanium powder hydrochloric acid solution with a pH of 4 and a 5% (w / w) acidified carbon nanotube aqueous solution. Add the acidified carbon nanotube aqueous solution to the titanium powder hydrochloric acid solution with stirring, and adjust the pH to 4 with hydrochloric acid. The mass ratio of titanium powder to acidified carbon nanotubes is 20:1.5. S3: Transfer to a reaction vessel ventilated with oxygen, react at 50°C for 25 hours, then filter and dry; S4: Placed in a tube furnace filled with hydrogen, reacted at 300℃ for 5 hours, cooled and then placed in a sintering furnace, held at 700℃ and 150MPa for 0.5 hours, cooled and crushed to obtain network-reinforced particles.

[0022] Example 4 The preparation method of the network-reinforced particles is as follows: S1: Take carbon nanotubes, soak them in a mixed acid solution for acidification for 6 hours, wash and dry them to obtain acidified carbon nanotubes; wherein, the mixed acid solution is prepared by mixing concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:3; S2: Prepare a 7% (w / w) titanium powder hydrochloric acid solution with a pH of 4 and a 6% (w / w) acidified carbon nanotube aqueous solution. Add the acidified carbon nanotube aqueous solution to the titanium powder hydrochloric acid solution with stirring, and adjust the pH to 4 with hydrochloric acid. The mass ratio of titanium powder to acidified carbon nanotube is 20:2. S3: Transfer to a reaction vessel ventilated with oxygen, react at 50°C for 25 hours, then filter and dry; S4: Placed in a tube furnace filled with hydrogen, reacted at 300℃ for 6 hours, cooled and then placed in a sintering furnace, held at 700℃ and 150MPa for 1 hour, cooled and crushed to obtain network-reinforced particles.

[0023] Example 5 The preparation method of the network-reinforced particles is as follows: S1: Take carbon nanotubes, soak them in a mixed acid solution for acidification for 7 hours, wash and dry them to obtain acidified carbon nanotubes; wherein, the mixed acid solution is prepared by mixing concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:4; S2: Prepare a titanium powder hydrochloric acid solution with a mass fraction of 8% and a pH value of 5 and an acidified carbon nanotube aqueous solution with a mass fraction of 7%. Add the acidified carbon nanotube aqueous solution to the titanium powder hydrochloric acid solution under stirring, and adjust its pH value to 5 with hydrochloric acid; the mass ratio of titanium powder to acidified carbon nanotube is 20:2.5. S3: Transfer to a reaction vessel ventilated with oxygen, react at 60°C for 25 hours, then filter and dry; S4: Placed in a tube furnace filled with hydrogen, reacted at 350℃ for 7 hours, cooled and then placed in a sintering furnace, held at 800℃ and 200MPa for 1 hour, cooled and crushed to obtain network-reinforced particles.

[0024] Example 6 The preparation method of the network-reinforced particles is as follows: S1: Take carbon nanotubes, soak them in a mixed acid solution for acidification for 7 hours, wash and dry them to obtain acidified carbon nanotubes; wherein, the mixed acid solution is prepared by mixing concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:4; S2: Prepare a 10% (w / w) titanium powder hydrochloric acid solution with a pH of 5 and a 5% (w / w) acidified carbon nanotube aqueous solution. Add the acidified carbon nanotube aqueous solution to the titanium powder hydrochloric acid solution with stirring, and adjust the pH to 5 with hydrochloric acid. The mass ratio of titanium powder to acidified carbon nanotube is 20:3. S3: Transfer to a reaction vessel ventilated with oxygen, react at 60°C for 30 hours, then filter and dry; S4: Placed in a tube furnace filled with hydrogen, reacted at 350℃ for 8 hours, cooled and then placed in a sintering furnace, held at 900℃ and 200MPa for 1 hour, cooled and crushed to obtain network-reinforced particles.

[0025] The mechanical properties of the mesh-reinforced particles before crushing were tested, and the results are shown in Table 1. Table 1 Example 1 328 23.8 Example 2 331 24.3 Example 3 332 26.1 Example 4 336 25.6 Example 5 338 27.2 Example 6 339 26.4 As can be seen from Table 1, Example 5 has the best mechanical properties. Therefore, the mesh-reinforced particles prepared in Example 5 were selected for subsequent tests.

[0026] The composition of the recycled aluminum alloy was determined to be as follows: Ti 0.20wt.%, Mn 0.11wt.%, Si 4.22wt.%, Mg 0.78wt.%, Fe 0.02wt.%, Cu 0.21wt.%, Al balance.

[0027] Example 7 A method for producing high-performance aluminum alloys using recycled aluminum, characterized by comprising the following steps: Step 1: Take the nitrogen-atomized recycled aluminum alloy material, add Fe elements with a particle size <48μm and La elements with a particle size <30μm, and perform planetary ball milling for 5 hours. The ball-to-material ratio is 10:1, the milling medium is acetone, and the rotation speed is 150 rpm. The Fe element content accounts for 3.2 wt.% and the La element content accounts for 1.0 wt.% of the recycled aluminum alloy material. Step 2: After ball milling, the powder is dried in air, and then a mesh reinforcing particle with a particle size of 0.1-1μm is added and mixed evenly; the mass ratio of recycled aluminum alloy to mesh reinforcing particles is 6:100. Step 3: Cold isostatic pressing at 100 MPa pressure; Step 4: Sinter at 650℃ for 5 h in a nitrogen atmosphere, and then hot extrude at 450℃ with an extrusion speed of 0.5 m / min.

[0028] Example 8 A method for producing high-performance aluminum alloys using recycled aluminum, comprising the following steps: Step 1: Take the nitrogen-atomized recycled aluminum alloy material, add Fe elements with a particle size <48μm and La elements with a particle size <30μm, and perform planetary ball milling for 5 hours. The ball-to-material ratio is 10:1, the milling medium is acetone, and the rotation speed is 150 rpm. The Fe element content accounts for 3.2 wt.% and the La element content accounts for 1.3 wt.% of the recycled aluminum alloy material. Step 2: After ball milling, the powder is dried in air, and then a mesh reinforcing particle with a particle size of 0.1-1μm is added and mixed evenly; the mass ratio of recycled aluminum alloy to mesh reinforcing particles is 6:100. Step 3: Cold isostatic pressing at 100 MPa pressure; Step 4: Sinter at 650℃ for 5 h in a nitrogen atmosphere, and then hot extrude at 450℃ with an extrusion speed of 0.5 m / min.

[0029] Example 9 A method for producing high-performance aluminum alloys using recycled aluminum, comprising the following steps: Step 1: Take the nitrogen-atomized recycled aluminum alloy material, add Fe elements with a particle size <48μm and La elements with a particle size <30μm, and perform planetary ball milling for 5 hours. The ball-to-material ratio is 10:1, the milling medium is acetone, and the rotation speed is 150 rpm. The Fe element content accounts for 3.2 wt.% and the La element content accounts for 1.5 wt.% of the recycled aluminum alloy material. Step 2: After ball milling, the powder is dried in air, and then a mesh reinforcing particle with a particle size of 0.1-1μm is added and mixed evenly; the mass ratio of recycled aluminum alloy to mesh reinforcing particles is 6:100. Step 3: Cold isostatic pressing at 100 MPa pressure; Step 4: Sinter at 650℃ for 5 h in a nitrogen atmosphere, and then hot extrude at 450℃ with an extrusion speed of 0.5 m / min.

[0030] Example 10 A method for producing high-performance aluminum alloys using recycled aluminum, comprising the following steps: Step 1: Take the nitrogen-atomized recycled aluminum alloy material, add Fe elements with a particle size <48μm and La elements with a particle size <30μm, and perform planetary ball milling for 5 hours. The ball-to-material ratio is 10:1, the milling medium is acetone, and the rotation speed is 150 rpm. The Fe element content accounts for 3.2 wt.% and the La element content accounts for 1.3 wt.% of the recycled aluminum alloy material. Step 2: After ball milling, the powder is dried in air, and then a mesh reinforcing particle with a particle size of 0.1-1μm is added and mixed evenly; the mass ratio of recycled aluminum alloy to mesh reinforcing particles is 4:100. Step 3: Cold isostatic pressing at 100 MPa pressure; Step 4: Sinter at 650℃ for 5 h in a nitrogen atmosphere, and then hot extrude at 450℃ with an extrusion speed of 0.5 m / min.

[0031] Example 11 A method for producing high-performance aluminum alloys using recycled aluminum, comprising the following steps: Step 1: Take the nitrogen-atomized recycled aluminum alloy material, add Fe elements with a particle size <48μm and La elements with a particle size <30μm, and perform planetary ball milling for 5 hours. The ball-to-material ratio is 10:1, the milling medium is acetone, and the rotation speed is 150 rpm. The Fe element content accounts for 3.2 wt.% and the La element content accounts for 1.3 wt.% of the recycled aluminum alloy material. Step 2: After ball milling, the powder is dried in air, and then a mesh reinforcing particle with a particle size of 0.1-1μm is added and mixed evenly; the mass ratio of recycled aluminum alloy to mesh reinforcing particles is 7:100. Step 3: Cold isostatic pressing at 100 MPa pressure; Step 4: Sinter at 650℃ for 5 h in a nitrogen atmosphere, and then hot extrude at 450℃ with an extrusion speed of 0.5 m / min.

[0032] Comparative Example 1 The difference between this comparative example and Example 8 is that no mesh-reinforcing particles are added, specifically: A method for producing high-performance aluminum alloys using recycled aluminum, comprising the following steps: Step 1: Take the nitrogen-atomized recycled aluminum alloy material, add Fe elements with a particle size <48μm and La elements with a particle size <30μm, and perform planetary ball milling for 5 hours. The ball-to-material ratio is 10:1, the milling medium is acetone, and the rotation speed is 150 rpm. The Fe element content accounts for 3.2 wt.% and the La element content accounts for 1.3 wt.% of the recycled aluminum alloy material. Step 2: The ball-milled powder is dried in air; Step 3: Cold isostatic pressing at 100 MPa pressure; Step 4: Sinter at 650℃ for 5 h in a nitrogen atmosphere, and then hot extrude at 450℃ with an extrusion speed of 0.5 m / min.

[0033] The sample was processed into a tensile specimen with a diameter of 6 mm × 30 mm and its mechanical properties were tested on a tensile testing machine.

[0034] Table 2 Example 7 623 474 9.8 Example 8 628 480 9.9 Example 9 629 481 10.1 Example 10 613 463 10.2 Example 11 632 483 9.5 Comparative Example 1 482 351 10.0

Claims

1. A method for producing high-performance aluminum alloys using recycled aluminum, characterized in that, Includes the following steps: Step 1: Take the recycled aluminum alloy material after nitrogen atomization, add Fe and La elements, and perform planetary ball milling; Step 2: After ball milling, the powder is dried in air, and then mesh reinforcing particles with a particle size of 0.1-1μm are added and mixed evenly. Step 3: Cold isostatic pressing at 100 MPa pressure; Step 4: Sinter at 600-650℃ for 5 h in a nitrogen atmosphere, and then hot extrude at 450℃; The composition of the recycled aluminum alloy is as follows: Ti 0.20wt.% Mn 0.11wt.% Si 4.22wt.% Mg 0.78 wt.% Fe 0.02wt.% Cu 0.21 wt.% Al balance; The Fe element has a particle size of <48μm, and the La element has a particle size of <30μm. The Fe element content accounts for 3.2 wt.% of the recycled aluminum alloy material, and the La element content accounts for 1.0-1.5 wt.% of the recycled aluminum alloy material. The mass ratio of the recycled aluminum alloy to the mesh reinforcing particles is (4-7):100; The method for preparing the network-reinforced particles is as follows: S1: Take carbon nanotubes, soak them in a mixed acid solution for acidification for 5-7 hours, wash and dry them to obtain acidified carbon nanotubes. S2: Prepare a titanium powder hydrochloric acid solution with a mass fraction of 3-10% and a carbon nanotube aqueous solution with a mass fraction of 3-7% and a pH value of 3-5. Add the acidified carbon nanotube aqueous solution to the titanium powder hydrochloric acid solution under stirring, and adjust its pH value to 3-5 with hydrochloric acid. S3: Transfer to a reaction vessel ventilated with oxygen, react at 40-60℃ for 20-30 hours, then filter and dry; S4: Place it in a tube furnace filled with hydrogen and react at 250-350℃ for 2-8 hours. After cooling, place it in a sintering furnace and hold it at 500-900℃ and 100-200MPa for 0.5-1 hours. After cooling and crushing, the mesh-reinforced particles are obtained.

2. The method for producing high-performance aluminum alloys using recycled aluminum according to claim 1, characterized in that, The ball milling time was 5 hours, the ball-to-material ratio was 10:1, the ball milling medium was acetone, and the rotation speed was 150 rpm.

3. The method for producing high-performance aluminum alloys using recycled aluminum according to claim 1, characterized in that, The extrusion speed of the hot extrusion molding is 0.5 m / min.

4. The method for producing high-performance aluminum alloys using recycled aluminum according to claim 1, characterized in that, The mixed acid solution is prepared by mixing concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:(2-4).

5. The method for producing high-performance aluminum alloys using recycled aluminum according to claim 1, characterized in that, The mass ratio of the titanium powder to the acidified carbon nanotubes is 20:(0.5-3).

Citation Information

Patent Citations

  • Different-dimensionality high-heat-conductivity material enhanced and polymer based composite and preparation method thereof

    CN105733191A

  • Preparation method of net structure titanium-silicon alloy phase reinforced TiAl-based composite

    CN109295336A